Adequate knowledge transformed to practice in relation to iron deficiency anaemia in pregnancy: experience from West Bengal - Sarkar, Arnabi; Lahiri, Arista; Chakraborty, Arup (International Journal Of Community Medicine And Public Health, 2018)
Background: High prevalence of anaemia among pregnant mothers in rural and urban West Bengal warrants a deeper observation. The current article thus, aims to explore the knowledge and practices towards iron deficiency anaemia (IDA) among the rural and urban antenatal mothers. Methods: An observational descriptive cross-sectional study was conducted among Fifty-four rural and seventy-one urban ante-natal mothers. A semi-structured interview schedule, Maternal and Child Protection Card (MCPC) and Laboratory evaluation reports were used. Results: Majority respondents were aged below 20 years and housewives. Around 59.25% rural and 66.19% urban mothers knew the meaning of ‘Anaemia’. Rural mothers consider pregnancy (54.55%) as the most common cause of iron deficiency anaemia, whereas, urban mothers think of dietary deficiency of iron rich foods (60.56%). Dietary knowledge was adequate, with 57.40% urban and 53.52% rural mothers consuming an extra home-cooked meal. Overall more than 90% mothers consumed green leafy vegetables. Majority mothers knew iron and folic acid (IFA) tablets should be consumed for at least 3 months (100 days) during pregnancy and should be continued after delivery. But 12.96% and 16.90% rural and urban mothers respectively did not take any tablet of IFA. Overall practice and knowledge were statistically associated in rural and urban settings with proper practice exceeding adequate knowledge in pooled estimate. Conclusions: The differences between urban and rural area in this study were marginal. But in some cases like IFA tablet consumption, Blood tests etc. there was a gap between knowledge and practice, which may actually indicate a lack of motivation.